Obstetric Characteristics and Management of Patients with Postpartum Psychosis in a Tertiary Hospital Setting - C. E. Shehu; M. A. Yunusa (Hindawi Limited, 2015)
Background. Postpartum psychosis is the most severe and uncommon form of postnatal affective illness. It constitutes a medical emergency. Acute management emphasizes hospitalization to ensure safety, antipsychotic medication adherence, and treatment of the underlying disorder. Objective. The aim of the study was to determine the obstetric characteristics and management of patients with postpartum psychosis in a tertiary centre in North-Western Nigeria. Methodology. This was a 10-year retrospective study. Records of the patients diagnosed with postpartum psychosis from January 1st, 2002, to December 31st, 2011, were retrieved and relevant data extracted and analyzed using the SPSS for Windows version 16.0. Results. There were 29 cases of postpartum psychosis giving an incidence of 1.1 per 1000 deliveries. The mean age of the patients was 20.6 ± 4 years. Twelve (55%) were primiparae, 16 (72.7%) were unbooked, and 13 (59%) delivered at home. All had vaginal deliveries at term. There were 12 (52.2%) live births, and 11 (47.8%) perinatal deaths and the fetal sex ratio was equal. The most common presentation was talking irrationally. Conclusion. There is need for risk factor evaluation for puerperal psychosis during the antenatal period especially in primigravidae and more advocacies to encourage women to book for antenatal care in our environment.